1979
DOI: 10.1007/bf00313946
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of sudden death with subarachnoid hemorrhage

Abstract: The mechanism of death in some patients with subarachnoid hemorrhage is cardiac arrhythmia. Prevention of cardiac arrhythmias by suitable drugs might save the life of patients whose brain is still good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…[16][17][18] The mechanisms leading to CA after SAH are well described, mainly due to the sudden increase of intracranial pressure. 8,[19][20][21][22] It is not clear whether CA with a need for CPR additionally deteriorates the already poor outcome of patients with SAH H&H grade 5.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The mechanisms leading to CA after SAH are well described, mainly due to the sudden increase of intracranial pressure. 8,[19][20][21][22] It is not clear whether CA with a need for CPR additionally deteriorates the already poor outcome of patients with SAH H&H grade 5.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental evidence has, for a century, suggested that the CNS has a role in cardiac dysrhythmias 128, 1351, the relevance of these experimental data to the clinical situation was first emphasized by Parizel in 1973 [llO]. His observations of supraventricular tachycardia, ectopic ventricular contractions, multifocal ventricular tachycardias, ventricular flutter, and ventricular fibrillation in subjects with subarachnoid hemorrhage [l 101 have been confirmed [25,35,40,49,111,1591 and extended to subjects with head injuries [60], cerebral ischemia [GO], and cerebral tumors [58], as well as those who have undergone neurosurgical procedures [58J The cardiac dysrhythmias in these conditions could occur with or without electrocardiographic signs of myocardial damage. Even though neural influences may generate the cardiac dysrhythmias, it is possible that the rhythm disturbances may be secondary to incipient cardiac damage caused by the neural influences.…”
Section: Cardiac Arrhythmias With Disease Of the Cns The Clinical Phementioning
confidence: 99%
“…The importance of these complicating cardiac arrhythmias to the overall prognosis of subjects with intracranial disease is profound. They presumably are a major cause of sudden death in patients with subarachnoid hemorrhage, which alone accounts for 4 to 5% of all nonviolent sudden deaths 11 111. One experimental study in cats with unilateral ischemia in the distribution of the left middle cerebral artery demonstrated major arrhythmias in 60% of the animals 1160).…”
Section: Cardiac Arrhythmias With Disease Of the Cns The Clinical Phementioning
confidence: 99%
See 1 more Smart Citation
“…Einleitung über vielfältige kardiale Rhythmusstörungen bis hin zu bedrohlichen Kammertachykardien nach Subarachnoidalblutungen (SAß) wurde berichtet (3, 8,14,16,17,18). Da aber bislang nur wenige Untersuchungen unter Anwendung einer kontinuierlichen EKG-Langzeitregistrierung erfolgten (15,17,18), mangelt es an einer detaillierten Erfassung und Analyse dieser Arrhythmien, insbesondere vor, während und nach hochakuten und unvorhersehbaren Ereignissen, wie Nachblutungen.…”
Section: Zusammenfassungunclassified